Factors Affecting the Quality of Life of Covid-19 Patients: Systematic Review - Fera Melinda; Iin Inayah; Hikmat Rudiyana; Cecep Eli Kosasih; Dede Supriyadi; Iwan Permana (GLOBAL HEALTH SCIENCE GROUP, 2025)
Covid-19 survivors generally still feel there are problems with physical and psychological decline. The effects of prolonged conditions have an impact on quality of life. Quality of life is an element that motivates life, individual physical and psychological experiences that can change individual existence in the future, social status and individual characteristics. This study aims to identify factors that affect the quality of life of Covid-19 patients. This study uses a Systematic Review method. The sample is 9 journals from 2020 to 2023 that meet the inclusion criteria with a feasibility test based on the Joanna Briggs Institute (JBI) Critical Appraisal Tools instrument. Then using PRISMA to select journals. Data from a systematic review conducted on 9 English or Indonesian journals that met the inclusion criteria. In general, the 9 journals have similarities and differences. the results of this study indicate that the factors of age, gender, marital status, employment status, education level, family support, comorbidities, physical disorders, mental disorders, weight affect the quality of life of covid 19 patients. Health insurance factors and income levels do not affect the quality of life of Covid-19 patients. Age, marital status, employment status, education level, family support, comorbidities, physical disorders, mental disorders, and weight factors affect the quality of life of Covid-19 patients. Gender, health insurance and income level factors do not affect the quality of life of Covid-19 patients.